Palm Oil Processing and Controversies over Its Health Effect: Overview of Positive and Negative Consequences - Urugo, Markos Makiso; Teshome, Paulos Getachew; Teka, Tilahun A.; Tringo, Tadele Tuba (Journal of Oleo Science, 2021)
Palm oil is the world’s most commonly used vegetable oil and extracted both from fruit and seed of palm tree. However, its high saturated fatty acid content raised controversies over consumption of the oil. Few scientific findings suggest it as a risk factor for cardiovascular disease and increased consumer’s awareness over healthy diet raised claim over it. So that, this article aimed to review literatures on palm oil extraction process and its positive and negative health consequences and besides suggest strategies for healthy diet. Literature search of relevant articles was conducted by using Google scholar, PubMed, Web of science, MEDLINE, World Health Organization library online catalogue, UNICEF library, Open access thesis and dissertations published between 2009 and 2021 explored. Study reports recommend that palmitic acid from vegetable source has less effect on blood total cholesterol and low density lipoprotein cholesterol level as compared to palmitic acid from animal source. In contrary tocotrienols of palm oil lowers blood bad cholesterol level by 7-38%. Moreover, palm oil triacylglycerol arrangement does not have a cardiovascular risk and evidences from available in vitro and in vivo studies are not sufficient enough to conclude palm oil as a causative agent for cardiovascular disease. For healthy diet consumers should avoid trans fatty acids, solid and semi solid oils. Finally, further studies recommended on mitigation strategies to minimize process induced toxicants of palm oil to acceptable level.